Effect of Urea Concentration on the Viscosity and Thermal Stability of Aqueous NaOH/Urea Cellulose Solutions. (23rd November 2016) - Huber, Tim; Starling, Katherine; Cen, Wanwen (Samantha); Fee, Conan; Dimartino, Simone
Abstract : Aqueous solutions of sodium hydroxide (NaOH) and urea are a known and versatile solvent for cellulose. The dissolution of cellulose occurs at subambient temperatures through the formation of a cellulose-NaOH-urea "inclusion complex" (IC). NaOH and urea form a hydrate layer around the cellulose chains preventing chain agglomeration. Urea is known to stabilize the solution but its direct role is unknown. Using viscometry and quartz crystal microbalance with dissipation monitoring (QCM-D) it could be shown that the addition of urea reduced the solutions viscosity of the tested solutions by almost 40% and also increased the gelation temperature from approximately 40°C to 90°C. Both effects could also be observed in the presence of additional cellulose powder serving as a physical cross-linker. Using Fourier transform infrared (FTIR) spectroscopy during heating, it could be shown that a direct interaction occurs between urea and the cellulose molecules, reducing their ability to form hydrogen bonds with neighbouring chains.